2019
DOI: 10.3389/fimmu.2019.02604
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Oxide Nanowires Exposure Induces a Distinct Inflammatory Response via CCL11-Mediated Eosinophil Recruitment

Abstract: High aspect ratio zinc oxide nanowires (ZnONWs) have become one of the most important products in nanotechnology. The wide range applications of ZnONWs have heightened the need for evaluating the risks and biological consequences to these particles. In this study, we investigated inflammatory pathways activated by ZnONWs in cultured cells as well as the consequences of systemic exposure in mouse models. Confocal microscopy showed rapid phagocytic uptake of FITC-ZnONWs by macrophages. Exposure of macrophages or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 64 publications
(77 reference statements)
1
6
0
Order By: Relevance
“…The size and surface area of ZnO-NPs have been linked to the severity of inflammatory illness caused by their exposure [ 235 ]. Previous research has shown that ZnO-NPs elicit a more severe inflammatory response than liquid zinc ions [ 236 ]. In various investigations, ZnO-NPs’ cytotoxic characteristics have been tested on human red and white blood cells.…”
Section: Toxicity Associated With Zno-npsmentioning
confidence: 99%
“…The size and surface area of ZnO-NPs have been linked to the severity of inflammatory illness caused by their exposure [ 235 ]. Previous research has shown that ZnO-NPs elicit a more severe inflammatory response than liquid zinc ions [ 236 ]. In various investigations, ZnO-NPs’ cytotoxic characteristics have been tested on human red and white blood cells.…”
Section: Toxicity Associated With Zno-npsmentioning
confidence: 99%
“…The magnitude of the inflammatory disease caused by the exposure to ZnO NPs has been associated with their size and surface area (Kalpana and Devi Rajeswari, 2018[ 24 ]). Earlier studies report that as compared to dissolved zinc ions, ZnO NPs can induce severe inflammatory response (Alghsham et al, 2019[ 3 ]). A series of experiments on human red blood cells and white blood cells have been conducted to evaluate the cytotoxic properties of ZnO NPs.…”
Section: Toxicity Issues Of Green Synthesized Npsmentioning
confidence: 99%
“…In a recent study, Alghsham et al also reported that ZnO NWs induce the production of TNF-α and IL-6 in cultured mouse macrophage cell line (RAW 264.7) and bone marrow macrophages obtained from the mice hind legs. From in vivo mouse model results, ZnO NWs facilitated the recruitment of macrophages and eosinophils into the lung and air-pouch [335].…”
Section: Immune Cellsmentioning
confidence: 99%